2017
DOI: 10.2196/jmir.8729
|View full text |Cite
|
Sign up to set email alerts
|

Designing Microblog Direct Messages to Engage Social Media Users With Suicide Ideation: Interview and Survey Study on Weibo

Abstract: BackgroundWhile Web-based interventions can be efficacious, engaging a target population’s attention remains challenging. We argue that strategies to draw such a population’s attention should be tailored to meet its needs. Increasing user engagement in online suicide intervention development requires feedback from this group to prevent people who have suicide ideation from seeking treatment.ObjectiveThe goal of this study was to solicit feedback on the acceptability of the content of messaging from social medi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 12 publications
3
16
0
Order By: Relevance
“…This is consistent with the position of Bryan et al (2018) who subsequently found that certain sequences in the content of social media could predict the cause and timeline of death by suicide. The conclusions of Bryan et al (2018) are in line with Tan et al (2017) who reported that whereas web-based interventions can be effective in the prevention of online suicide, it is also imperative to increase user engagement with online information and discussion groups.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…This is consistent with the position of Bryan et al (2018) who subsequently found that certain sequences in the content of social media could predict the cause and timeline of death by suicide. The conclusions of Bryan et al (2018) are in line with Tan et al (2017) who reported that whereas web-based interventions can be effective in the prevention of online suicide, it is also imperative to increase user engagement with online information and discussion groups.…”
Section: Introductionsupporting
confidence: 69%
“…The results of our empirical analyses have significantly improved the narratives in the aforementioned exploratory and country-specific studies in three key ways. First, they complemented the description by Tan et al (2017) and other country-specific studies by confirming the policy relevance of the negative association between social media and crime. This global dimension can lead to the adoption of more holistic policies that are applicable to a 1 The positioning and design of this paper is consistent with the extant recent empirical and theoretical studies on the relevance of information technology in: (i) enhancing conditions for human development (Afutu-Kotey et al, 2017;Bongomin et al, 2018 ;Asongu and Boateng, 2018;Gosavi, 2018;Hubani and Wiese, 2018;Minkoua Nzie et al, 2018;Isszhaku et al, 2018;Abor et al, 2018;Muthinja and Chipeta, 2018;Nwachukwu, 2018a, 2018b)and improving society with opportunities for human emancipation (Kreps and Kimppa, 2015;Tatnall, 2015;Lennerfors et al, 2015;Patrignani and Whitehouse, 2015;Aricat, 2015;Lahtiranta et al, 2015;Tchamyou, 2017Tchamyou, , 2018Tchamyou and Asongu, 2017).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…By sharing personal experiences of their mental illness, Facebook users provided informational and emotional support to other group members that may not be available from the receivers own social network or professionals, in line with previous research [18,19,34]. This form of support may lead to increased feelings of connectedness for the receiver [67,78], and could potentially reduce feelings of social isolation [22][23][24]74], and may offer hope to people using Facebook for their mental illness [76], thus empowering them to seek help or take positive action. From the findings, it was noted that the UK sample tended to show a slightly higher level of self-disclosure.…”
Section: Principle Findingsmentioning
confidence: 64%
“…Blogging has been found to increase the likelihood of engagement with suicide prevention intervention [67], and to be an effective tool for engaging young people with mental health and substance use intervention programmes [68]. In spite of potential concerns relating to confidentiality and stigmatisation, people are using blogging as a way to reduce stigma through 'defiant disclosure' [69].…”
Section: Mobile Apps For Mental Health Supportmentioning
confidence: 99%